PENGIRIMAN TENAGA KERJA MIGRAN SEBAGAI SALAH SATU BENTUK PERBUDAKAN MODERN DARI TINDAK PIDANA PERDAGANGAN ORANG - Henny Nuraeny (Jurnal Hukum dan Peradilan, 2015)
Indonesia in one of the sending country of labour migrants in Asia. The delivery of migrant workers are generally carried out in a variety of ways, legal or the illegal. The delivery of migrant workers illegal is always associated with slavery as a form of criminal act of trafficking. Criminal act of trafficking can happen in various forms, but usually aims to exploits victims in order to benefit. Though a variety of strategic plan in prevention efforts already planned and implemented, but the reality in people are still many obstacles faced in the prevention of criminal trafficking with the mode of delivery of migrant workers. Therefore necessary cooperation and united fleets weapons between all components of society, law enforcement officers and government.Keywords: Migrant Worker, Slavery, Trafficking